Free fatty acids repress small heterodimer partner (SHP) activation and adiponectin counteracts bile acid‐induced liver injury in superobese patients with nonalcoholic steatohepatitis12. Issue 4 (8th April 2013) - Bechmann, Lars P.; Kocabayoglu, Peri; Sowa, Jan‐Peter; Sydor, Svenja; Best, Jan; Schlattjan, Martin; Beilfuss, Anja; Schmitt, Johannes; Hannivoort, Rebekka A.; Kilicarslan, Alpaslan; Rust, Christian; Berr, Frieder; et al.
Abstract Nonalcoholic fatty liver disease (NAFLD) is the most common liver disease in industrialized countries and may proceed to steatohepatitis (NASH). Apoptosis and free fatty acid (FFA)‐induced lipotoxicity are important features of NASH pathogenesis. We have shown a hepatoprotective effect of adiponectin in steatotic livers of hepatitis C virus (HCV) patients and recent data links bile acid (BA) metabolism to the pathogenesis of NAFLD. The aim of this study was to identify potential interactions between BA and FFA metabolism in NAFLD. Liver biopsies and serum samples from 113 morbidly obese patients receiving bariatric surgery, healthy individuals, and moderately obese NAFLD patients were studied. Serum FFA, BA, and M30 were increased in NASH versus simple steatosis, while adiponectin was significantly decreased. The NAFLD activity score (NAS) score correlated with BA levels and reversely with adiponectin. Adiponectin reversely correlated with CD95/Fas messenger RNA (mRNA) and hepatocellular apoptosis. The BA transporter high‐affinity Na+/taurocholate cotransporter (NTCP) and the BA synthesizing enzyme cholesterol 7 alpha‐hydroxylase (CYP7A1) were significantly up‐regulated in obese patients and hepatoma cells exposed to FFA. Up‐regulation of NTCP and CYP7A1 indicate failure to activate small heterodimer partner (SHP) upon farnesoid X receptor (FXR) stimulation by increasing BA concentrations. In line with the NAS score, adiponectin levels were reversely correlated with BA levels. Adiponectin correlated with NTCP and affects Cyp7A1 expression both in vivo and in vitro. Conclusion: BA synthesis and serum BA levels correlated with disease severity in NAFLD, while adiponectin is reversely correlated. FFA exposure prevented SHP‐mediated repression of NTCP and Cyp7A1 expression, which lead to increased BA synthesis and uptake. In NASH, BA accumulation induced hepatocyte cell death and late FXR activation failed to prevent hepatocyte injury due to decreased adiponectin levels. Early treatment with FXR ligands and/or adiponectin‐receptor agonists might prevent NASH. (HEPATOLOGY 2013;57:1394–1406)